SAT0170 A NOVEL FORMULATION OF CT-P13 FOR SUBCUTANEOUS ADMINISTRATION: 30 WEEK RESULTS FROM A PART 2 OF PHASE I/III RANDOMIZED CONTROLLED TRIAL IN PATIENTS WITH RHEUMATOID ARTHRITIS. (June 2019) - Westhovens, Rene; Wiland, Piotr; Zawadzki, Marek; Ivanova, Delina; Berrocal, Alfredo; Chalouhi, Elias; Balázs, Éva; Shevchuk, Sergii; Eliseeva, Larisa; Stanislavchuk, Mykola; Yatsyshyn, Roman; Lee, Sangjoon; et al.
Abstract : Background: CT-P13 subcutaneous (SC) formulation showed comparable efficacy and safety with CT-P13 intravenous (IV) formulation in rheumatoid arthritis (RA) 1 and Crohn's disease 2 preliminary studies (Part 1). Objectives: The purpose of this study was to demonstrate non-inferiority (NI) of efficacy and compare safety profiles of CT-P13 SC to CT-P13 IV in RA patients over 30 weeks of Part 2. Methods: In this randomized, controlled, double blinded, phase I/III study, RA patients received CT-P13 IV 3 mg/kg at Weeks 0 and 2 and were randomized at Week 6 to receive CT-P13 SC 120 mg every 2 weeks or CT-P13 IV 3 mg/kg every 8 weeks. From Week 30, all patients received CT-P13 SC 120 mg every 2 weeks. The primary efficacy endpoint, change of DAS28 (C-reactive protein [CRP]) from baseline to Week 22, was analyzed by using an analysis of covariance (ANCOVA). Non-inferiority is to be concluded if the lower bound of the 95% CI for the treatment difference in the change of DAS28 (CRP) from baseline to Week 22 is greater than the pre-specified NI margin of -0.6. Results: A total of 362 patients were enrolled, of whom 348 were randomly assigned at Week 6 into 2 treatment arms in a 1:1 ratio (169 and 179 patients in SC 120 mg and IV 3 mg/kg arms, respectively). The mean change of DAS28 (CRP) from baseline to Week 22 was similar between the arms. The lower limit of two-sided 95% CI (0.03) was greater than the pre-specified NI margin (-0.6) which indicated NI of SC 120 mg compared to IV 3 mg/kg (Table 1 ). Additional efficacy including ACR responses were similar between two treatment arms up to Week 22 with slightly higher response rate trend observed in SC 120 mg arm at Week 30 (Figure 1 ). The safety profiles which occurred after study drug administration at Week 6 in SC 120 mg arm were generally comparable to IV 3 mg/kg arm. All of injection site reactions were grade 1 or 2 in intensity. Majority of administration-related reactions (ARRs) were grade 1 or 2 in intensity except 1 patient in IV 3 mg/kg arm who experienced grade 3 ARR and was withdrawn from the study due to this event (Table 2 ). Conclusion: The study demonstrated NI of efficacy for CT-P13 SC to the CT-P13 IV. Also, CT-P13 SC showed similar efficacy and safety profiles to CT-P13 IV up to Week 30. CT-P13 SC could provide a favorable benefit to patients with an alternative convenient way of administration. References: [1] Westhovens R, et al. Annals of the Rheumatic Diseases 2018;77(-):315 (suppl2) [2] Schreiber, S, et al. Gastroenterology2018;154(6):S-1371 Disclosure of Interests: Rene Westhovens Grant/research support from: Bristol-Myers Squibb, Consultant for: Celltrion, Galapagos-Gilead, Piotr Wiland Speakers bureau: Novartis, Pfizer, Abbvie, Gedeon-Richter, Lilly, Roche and Sandoz, Marek Zawadzki Grant/research support from: Celltrion, Inc., Delina Ivanova Grant/research support from: Celltrion, Inc, PPD, Quintiles, Egis Pharmaceuticals, and Pfizer., Alfredo Berrocal Grant/research support from: Celltrion, Inc., Elias Chalouhi Grant/research support from: Celltrion, Inc., Éva Balázs Grant/research support from: Celltrion, Inc., Consultant for: Merck and Amgen, Sergii Shevchuk: None declared, Larisa Eliseeva Grant/research support from: Celltrion, Inc., Mykola Stanislavchuk Grant/research support from: AstraZeneca, Celltrion, Galapagos, Genentech, GlaxoSmithKline, Human Genome, Lilly, MedImmune, Pfizer, Roche and UCB, Roman Yatsyshyn Grant/research support from: Celltrion, Inc., SangJoon Lee Shareholder of: Celltrion, Inc., Employee of: Celltrion, Inc., JeeHye Suh Employee of: Celltrion, Inc., SeulGi Lee Employee of: Celltrion, Inc., Yunah Kim Employee of: Celltrion, Inc., DaeHyun Yoo Grant/research support from: Celltrion, Inc., Consultant for: Celltrion, Inc.